In Enhancing Preservice Teachers’ Assessment Literacy: Focus on Knowledge Base, Conceptions of Assessment, and Teacher Learning - Atjonen, Päivi; Pöntinen, Susanna; Kontkanen, Sini; Ruotsalainen, Päivi (Frontiers in Education, 2022)
Assessment has a critical and time-consuming role in the teaching profession. However, teachers generally possess low levels of assessment knowledge and skills, with their understanding more about the culturally and historically established summative approach than the “assessment for learning” one. Therefore, developing student teachers’ assessment literacy in initial teacher education (ITE) is important. In the present intervention study, as part of the theoretical-pedagogical studies in ITE, student teachers' assessment literacy was examined. Deductive content analyses of students' (N = 168) written diaries were conducted applying a conceptual framework of teacher's assessment literacy in practice (TALiP). Based on the results, the students' assessment knowledge base and assessment conceptions were promisingly versatile and indicated a rich awareness of the broad nature of assessment. However, the key findings also suggest that assessment is not an easy topic for student teachers to discuss with peers. It can be concluded that even short ITE interventions can open student teachers to the various pedagogical inputs and outputs of assessment. Therefore, authentic assessment experiments with pupils must be available during teaching practice periods.